Afterlife: A History of Life after Death - Almond, Philip C. (I.B.Tauris, 2016)
List of Plates -- Acknowledgements -- Prologue -- Chapter One -- The spirits of the dead -- Rewards and punishments -- Go directly to Paradise -- Paradise not quite regained yet -- Chapter Two -- Dante's limbo -- The Limbo of the Infants -- The Limbo of the Fathers -- 'He descended into hell' -- Chapter Three -- Composite creatures -- The origin of the soul -- Time and eternity -- Resurrected bodies -- Flesh and bones -- Sharks and cannibals -- Apocalypse soon -- Chapter Four -- 'Blessed be God' -- Particular judgements -- A fiery purging -- Praying for the dead -- Craving your indulgence